PROBLEM ISSUES IN THE PROCESS IMPLEMENTATION BUDGET OF THE MINISTRY OF DEFENSE OF UKRAINE FOR 2014–2020 YEARS - Syzov, A.; Artiushenko, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
This article analyzes the budget of the Ministry of Defense of Ukraine for the 2014–2020 years in accordance with the reporting data of the State Treasury Service of Ukraine and factors that have an influence on its formation. The basic principles according to which the organization of the government spending in Ukraine is carried out, the concept of managers budgetary funds and financial – planning documents which are created in the course of its activity are researched. It is established that in the State Budget of Ukraine expenditures on the Ministry of Defense of Ukraine have a tendency to growth for the whole study period. Providing the effective use of budget funds is one of the key problems of budget performance, which is typical for most countries of the world. In order to determine the level of completeness and efficiency budget appropriate budget manager, were analyzed an expenditures Ministry of Defense of Ukraine for 2014–2020 years by months and also the balance of unused financial resources for the years was determined, and so was confirmed that there are issues that have a high degree of negative influence for the process of budget planning and performance. Analysis of the structure of defense budget for 2009–2021 was carried out and modern approaches for determining the optimal structure of defense budget were considered. The considerable unbalanced allocation of expenditures of the Ministry of Defense of Ukraine in terms of months was emphasized. In the process of studying the state of implementation of the budget of the Ministry of Defense of Ukraine, topical issues were identified that need further research, namely: ensuring the appropriate level of financing of the defense forces, the structure of the defense budget, the system of evaluation and monitoring of the effectiveness of budget programs, the autonomy of the main managers budget funds in the process of implementing the expenditure part of the budget. Possible ways of optimization certain issues in the process of budget planning and execution for the increasing level of completeness and effectiveness of performance budget in the direction of state defense are proposed. This article identify direction for further research: improving the existing theoretical and practical tools for providing effective use of limited financial resources to support defense of the state, and also research of foreign experience about implementation of the program - target method budget performance.